Предмет: Математика, автор: linagoncharova2005

УПРОСТИТЕ ВЫРАЖЕНИЕ
1) sina/1+cosa + sina/1-cosa
2) tg^2a * cos^2a + ctg^2a * sin^2a

Ответы

Автор ответа: 13deir
1

Ответ:

1) \frac{2}{sina}  2) 1

Пошаговое объяснение:

1) sina/1+cosa + sina/1-cosa=(sina*(1-cosa)+sina*(1+cosa)):(1+cosa)*(1-cosa)=(sina-sina*cosa+sina+sinacosa):(1-cos^2a)=\frac{2sina}{sin^{2} a} =\frac{2}{sina}

tg^{2} a*cos^{2}a+ctg^{2} a*sin^{2}a=\frac{sin^{2}a }{cos^{2}a }*cos^{2}a+\frac{cos^{2}a }{sin^{2}a }*sin^{2}a=sin^{2} a+cos^{2}a=1

Похожие вопросы
Предмет: Русский язык, автор: oli1111
Предмет: Химия, автор: Agagadir
Предмет: Химия, автор: Agagadir